Avaliação da importância a da produção de ROS e do eixo de controle da liberação de cálcio na osteoclastogênese - Ribeiro, Mariana Soares Pena (2016)
Species active oxygen (ROS) are produced by an enzyme complex called NADPH oxidase (NOX) which is able to reduce oxygen using NADPH as the substrate. It is known that ROS are involved in the differentiation of osteoclasts. To evaluate the influence of NOX2 and ROS on osteoclast formation, Apocynin (APO) was used as a NOX2 inhibitor (NADPH isoform 2) and N-acetyl-cysteine (NAC) as a reductant of intracellular ROS levels. The oscillation of Ca is also important in the final moments of osteoclast formation and it was analyzed if NOX2 and ROS were involved in this mechanism. The results demonstrated that treatment with APO reduced the number of TRAP cells positive and the expression of TRAP, which suggests that the reduction of the number of osteoclasts is related to the decrease of TRAP. However, treatment with NAC didn’t reduce the number of TRAP-positive in addition to increasing the expression of TRAP. In addition, it is believed that osteoclastogenesis is dependent on NOX2 by other pathways besides ROS production and RANK expression, pathways that were altered by both APO and NAC, but with a different impact on the number of osteoclasts. In the EEIG1 pathway, it was observed that the APO treatment reduced the expression of this pathway, whereas the treatment with NAC increased this expression, thus it was verified that NOX2 reduces osteoclastogenesis in a way not yet known. The ERK1 and TPC2 pathways presented a biphasic behavior in relation to the treatments. On the other hand, we hypothesized that treatment with NAC would delay or inhibit late osteoclastogenesis, in addition to suggesting that the participation of NOX2 in the formation of osteoclasts would not be related only to the production of ROS. Therefore, we also suggest that the participation of the RANKL/RANK/NOX2/ROS pathways as RANKL/RANK/NOX2/Rac1/PLCy1 are important for osteoclastogenesis, with only one of these being insufficient for osteoclastogenesis. In the treatments with APO and NAC in BMC we obtained a reduction of the area of the osteoclasts, as well as the reduction of the expression of DC-STAMP. It is concluded that NOX2 participates in the process of osteoclastogenesis in several signaling pathways and is related in addition to the production of ROS and other processes not yet known, but essential to decrease the formation of osteoclasts.